2012
DOI: 10.1097/bpo.0b013e31823d8338
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes as a Function of Meniscal Stability in the Discoid Meniscus

Abstract: Level III: Therapeutic Study, Retrospective, Comparative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
3
34
0
2
Order By: Relevance
“…Previously, several authors investigated the outcomes of arthroscopic saucerization and reported promising results with few complications [3,4,6,[8][9][10][11][12][13][14][15][16][17][18][19]. However, prognostic factors affecting the final outcomes are not well studied in relevant literature.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, several authors investigated the outcomes of arthroscopic saucerization and reported promising results with few complications [3,4,6,[8][9][10][11][12][13][14][15][16][17][18][19]. However, prognostic factors affecting the final outcomes are not well studied in relevant literature.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, current recommendation for symptomatic DLM is arthroscopic partial meniscectomy and reshaping DLM into a crescent-shaped normal meniscus, also called 'saucerization.' In case of rim instability, which is particularly present in Wrisberg type DLM, reattachment of meniscus to the nearby capsule should be performed simultaneously [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment has evolved to arthroscopic preservation of as much stable meniscal tissue as possible with repair of peripheral tears causing meniscal instability (Figure 3). Carter et al 20 published their preliminary results in 51 symptomatic discoid meniscal surgeries, which showed that adding peripheral rim repair did not increase complications or affect preliminary surgical results at average follow-up of 15 months.…”
Section: Symptomatic Discoid Lateral Meniscusmentioning
confidence: 97%
“…Surgery may include central meniscus tear excision and saucerisation along with repair of any instability of the periphery of the meniscal rim. 19 Asymptomatic discoid menisci can safely be left alone. 20 Patella instability Patella dislocation is the most common injury sustained around the knee in adolescents, with a prevalence of 0.7 per 1000.…”
Section: Meniscal Tearsmentioning
confidence: 99%